2004
DOI: 10.1002/hyp.1379
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrologic regime and vegetation on phosphorus retention in Everglades stormwater treatment area wetlands

Abstract: Abstract:The Florida (USA) Everglades ecosystem has been impacted due to increased loading of nutrients, in particular phosphorus (P), primarily from adjacent agricultural areas. Consequently, restoration measures involve the establishment of stormwater treatment areas (STAs) comprising a series of constructed wetlands. A series of mesocosms were established at the inflow of the Everglades Nutrient Removal Project wetland, the first such STA constructed. These mesocosms were designed to mimic STAs, as they ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Phosphorus in periphyton mats provides the best metric for detecting phosphorus enrichment in freshwater, which is consistent with the rapid uptake of labile phosphorus from the water column by both biotic and abiotic components of the periphyton detected in radioisotope tracing studies (Scinto and Reddy, 2003). Yet previous studies have reported large variations in the phosphorus removal efficiency of periphyton across space and time (e.g., Vermaat et al, 2000;White et al, 2004;Jakub et al, 2010;Derrick, 2014 water quality function of periphyton, it is necessary to thoroughly understand the various components of and mechanisms involved in phosphorus cycling. Nanhu, Donghu, Niuchaohu, and Liangzihu are four typical shallow lakes with different trophic status in Wuhan City, Hubei province, China.…”
Section: Introductionsupporting
confidence: 74%
“…Phosphorus in periphyton mats provides the best metric for detecting phosphorus enrichment in freshwater, which is consistent with the rapid uptake of labile phosphorus from the water column by both biotic and abiotic components of the periphyton detected in radioisotope tracing studies (Scinto and Reddy, 2003). Yet previous studies have reported large variations in the phosphorus removal efficiency of periphyton across space and time (e.g., Vermaat et al, 2000;White et al, 2004;Jakub et al, 2010;Derrick, 2014 water quality function of periphyton, it is necessary to thoroughly understand the various components of and mechanisms involved in phosphorus cycling. Nanhu, Donghu, Niuchaohu, and Liangzihu are four typical shallow lakes with different trophic status in Wuhan City, Hubei province, China.…”
Section: Introductionsupporting
confidence: 74%
“…These vegetation-induced changes can result in lower concentrations of suspended sediment (Braskerud 2001;Leonard and Reed 2002), greater sediment deposition rates , or decreased resuspension of sediments in densely vegetated portions of wetlands (Braskerud 2001). These dynamics of suspended sediment also are important for controlling phosphorus (P) cycling and transport in aquatic ecosystems (Fox 1993;Froelich 1988;Kadlec 1999), with intermediate removal rates of particulate P compared to faster soluble reactive P removal or slower dissolved organic P removal in wetlands (Davis 1981;Farve et al 2004;White et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…On average, alum significantly reduced SRP concentrations to three times lower than the controls (no alum). There was 40% lower DOP concentrations compared with the controls demonstrating that alum caused flocculation of dissolved organic P compounds, which are generally the most difficult forms of P to remove in a treatment wetland (White et al, 2004). There was a similar trend seen for the TDN, which include ammonium (∼5%) and DON (∼95%), with greater removal of DON fraction with alum dosing.…”
Section: Discussionmentioning
confidence: 99%